Activity of cinnamaldehyde, carvacrol and thymol combined with antifungal agents against Fusarium spp. Issue 5 (3rd September 2021) - Venturini, Tarcieli Pozzebon; Rossato, Luana; Chassot, Francieli; De Azevedo, Maria Isabel; Al-Hatmi, Abdullah M. S.; Santurio, Janio Morais; Alves, Sydney Hartz
ABSTRACT: Fusarium spp. are able to cause a wide range of opportunistic infections in both immunocompromised and immunocompetent individuals. Thus, new therapeutic options should be considered. We evaluated the antifungal activity of three phytocompounds (cinnamaldehyde, CIN; carvacrol, CRV; and thymol, THY), as well as their activities when combined with amphotericin B (AMB), caspofungin (CAS), itraconazole (ITC) and voriconazole (VRC) against 20 clinical isolates of  Fusarium . Broth microdilution (M38-A2) and checkerboard methodologies were used to obtain MICs (Minimum inhibitory concentration) and FICIs (Fractional Inhibitory Concentration Index), respectively. The MICs observed for the phytocompounds were: 20–80 for CIN, 40-> 320 for CRV and 40–320 µg/mL for THY. The most effective combinations (synergism rates) were: THY + CAS (96%), CRV + CAS (88%), THY + AMB (76%), CRV + AMB (68%), THY + VRC (68%) and CRV + VRC (60%). Our findings suggest that CRV and THY have potent activity when combined with CAS, AMB or VRC.